Meta-Analysis of Clinical Trials That Evaluate the Effectiveness of Hospital-Initiated Postdischarge Interventions on Hospital Readmission. Issue 6 (November 2017) - Branowicki, Patricia M.; Vessey, Judith A.; Graham, Dionne A.; McCabe, Margaret A.; Clapp, Alison L.; Blaine, Kevin; O'Neill, Margaret R.; Gouthro, Julie A.; Snydeman, Colleen K.; Kline, Nancy E.; Chiang, Vincent W.; Cannon, Courtney; et al.
Abstract : Abstract: Under pressure to avoid readmissions, hospitals are increasingly employing hospital-initiated postdischarge interventions (HiPDI), such as home visits and follow-up phone calls, to help patients after discharge. This study was conducted to assess the effectiveness of HiPDI on reducing hospital readmissions using a systematic review of clinical trials published between 1990 and 2014. We analyzed twenty articles on HiPDI (from 503 reviewed abstracts) containing 7, 952 index hospitalizations followed for a median 3 months (range 1–24) after discharge for readmission. The two most common HiPDI included follow-up phone calls ( n = 14, 70%) or home visits ( n = 11, 55%); eighty-five percent ( n = 17) of studies had multiple HiPDI. In meta-analysis, exposure to HiPDI was associated with a lower likelihood of readmission (odds ratio [OR], 0.8 [95% CI, 0.7–0.9]). Patients receiving ≥2 postdischarge home visits or ≥2 follow-up phone calls had the lowest likelihood of readmission (OR, 0.5 [95% CI, 0.4–0.8]). Hospital-initiated postdischarge interventions seem to have an effect on reducing hospital readmissions. Together, multiple home visits and follow-up phone calls may be the most effective HiPDI to reduce hospital readmission.